IDENTIFICATION OF SUBSURFACE SOIL LAYERS USING GEOELECTRIC METHOD IN ENVIRONMENT 2 OF RIANIATE VILLAGE TAPANULI SELATAN REGENCY - Kristina; Doloksaribu, Maryati Evivani (EINSTEIN (e-Journal), 2024)
A research on the identification of subsurface layers using the schlumberger configuration geoelectric method has been carried out on the coast of Lake Siais Environment 2, Rianiate Village, South Tapanuli Regency. With the aim of knowing the identification of subsurface layers, rock types, resistivity values, 2D contour cross section using Res2DinV software and the relationship of the resistivity value of the subsurface layer with climatology data. The results collected on 3 tracks with a length of 155m have a resistivity value of 133Ωm – 3389Ωm on the first track, the second track has 140Ωm - 2768Ωm and the third track 705Ωm - 4358Ωm. The results were processed by Res2DinV software to obtain a 2D cros section. As for the relationship of field data to BMKG data, rainfall has decreased from the last five years from 3744 mm – 3534 mm/year, humidity has decreased by 0,01762% each year, air temperature has increased by 0,09270 0C. From these results, resulting in changes in resistivity value in the subsurface.